Yield of muskmelon (Cucumis melo L.) with plastic mulch: applying vermicompost a a nutrient source - Moreno- Reséndez, Alejandro; Reyes-Carrillo, José Luis; López-Salazar, Rubén; Leos-Escobedo, Lucio; Espinoza-Banda, Armando (Ecosistemas y Recursos Agropecuarios, 2023)
The application of vermicompost (VC) favors the growth, development and productivity of many crops, so the objective of this study was to compare synthetic fertilization with the application of VC in melon yield with plastic mulch. Planting was done during the spring-summer 2019, VC was applied at the rate of 15 and 30 t·ha−1 and 240-80-00 t·ha−1 of N-P-K in 2 x 8 m melon beds with black plastic covers and drip irrigation. A completely randomized design was used and was compared with the DMS0.05 test. The polar and equatorial diameters, pulp thickness, fruit weight and yield showed significant differences, but soluble solids did not show difference. The highest yield of 31,362 t·ha−1 was registered with application of 30 t·ha−1, which indicates that this dose managed to cover the nutritional demand without applying synthetic fertilizers.
Keywords: fertilization, organic manures, plant nutrition, worm castings, yield